Strategic communication for startups: analysis of its intervention in the use of social networks. - Córdova Camacho, Jhoana; Victoria-Mas, Juan Salvador; Altamirano Benítez, Verónica (Journal of Positive Psychology, 2022)
The objective of this study is to identify the variables that are related to digital social networks for the consumption promoted by startups. Among the theoretical references is the study of the relationship between digital social networks and communication, and the conceptual and critical analysis of startups. The research focused on the study of multiple cases to obtain the necessary information, and semi structured interviews were conducted in a virtual environment to 10 Latin American startups. In order to identify the variables, it was necessary to create categories and from these the following variables were derived: communication, relationship, disclosure, speed, customers (users), interactivity, coverage, cost, diagnosis, content of publications and monitoring. The answers obtained from the startups contributed to the understanding of digital social networks, startups and communication through the variables created by this triangulation.
https://journalppw.com/index.php/jppw/openaccess
Keywords: Redes sociales en internet; Emprendedores; Nuevas empresas; Startups; Social networks; Digital communication; Variables